COLLOCATIONAL PATTERNS AND SENSE RELATIONS IN THE EXPLICATION OF MEANING IN ARMAH’S NOVELS - GODWIN F. AKPAN (International Studies Journal)
When literary writers write, they do so with the aim of conveying meaning. And the tool which gives expression to their thought is language. At various time, literary writers including the 20th century writers like Ayi Kwei Armah has deployed and manipulated language to suit his thematic concerns. This paper therefore seeks to study one of such language manipulations – collocation. It established that collocation is a habitual juxtaposition of a particular word with another word or words with a frequency greater than chance. However, from the study it is revealed that more often than not, Armah, violated this prism by using lexical items which normally should not co-occur. But instead of seeing this as a language error, it should be seen as novel and which contribute to the understanding of meaning. It analysed three of Armah’s novels using the theories of reader-response and discourse analysis. The data analysed were randomly selected. It concludes that Armah relied on both habitual co-occurrence and abnormal co-occurrence of lexical items to convey his meanings. Armah has enjoyed a lot of literary analysis and criticisms, this present work seeks to study scientifically his word choice as a further contribution to the corpus literature (both literary and linguistic) on him. We opined that rather than see Armah’s choice of words as bothering on obscenities, his choices should appreciated given the burden of the themes he seeks to share with his readers.